Prevalence and risk factors for colonization by extended-spectrum β-lactamase-producing or ST 131 Escherichia coli among asymptomatic adults in community settings in Southern Taiwan - Wu PC; Wang JL; Hsueh PR; Lin PH; Cheng MF; Huang IF; Chen YS; Lee SS; Guang-Yuan M; Yu HC; Hsu CL; Wang FW; et al. (Infection and Drug Resistance, 2019)
Pin-Chieh Wu,1,2,* Jiun-Ling Wang,3,4,* Po-Ren Hsueh,5 Po-Hsiang Lin,6 Ming-Fang Cheng,7–10 I-Fei Huang,7 Yao-Shen Chen,8,11 Susan Shin-Jung Lee,8,11 Mar Guang-Yuan,1,11 Hsien-Chung Yu,1,8,11–12 Chiao-Lin Hsu,1,2 Fu-Wei Wang,2,13 Chi-Shen Chen,1 Chih-Hsin Hung,9 Wen-Chien Ko3,41Department of Physical Examination Center, Kaohsiung Veterans General Hospital, Kaohsiung, Taiwan; 2Department of Nursing, Meiho University, Pingtung, Taiwan; 3Department of Internal Medicine, National Cheng Kung University Hospital, Tainan, Taiwan; 4Department of Medicine, College of Medicine, National Cheng Kung University, Tainan, Taiwan; 5Departments of Laboratory Medicine and Internal Medicine, National Taiwan University Hospital, National Taiwan University College of Medicine, Taipei, Taiwan; 6Department of Emergency Medicine, Kaohsiung Veterans General Hospital, Kaohsiung, Taiwan; 7Department of Pediatrics, Kaohsiung Veterans General Hospital, Kaohsiung, Taiwan; 8School of Medicine, National Yang-Ming University, Taipei, Taiwan; 9Department of Chemical Engineering and Institute of Biotechnology and Chemical Engineering, I-Shou University, Kaohsiung, Taiwan; 10Department of Nursing, Fooyin University, Kaohsiung, Taiwan; 11Department of Internal Medicine, Kaohsiung Veterans General Hospital, Kaohsiung, Taiwan; 12Institute of Health Care Management, Department of Business Management, National Sun Yat-sen University, Kaohsiung, Taiwan; 13Department of Family Medicine, Kaohsiung Veterans General Hospital, Kaohsiung, Taiwan*These authors contributed equally to this workPurpose: Fecal carriage of extended-spectrum β-lactamase-producing Escherichia coli (ESBL-EC) is common in Asia, especially in China and Southeast Asia. There are no data about fecal carriage of ESBL-EC and mcr-1-positive E. coli in Taiwan, and few studies focusing on the risk factors of asymptomatic fecal carriage of epidemic ST131 E. coli have been published.Patients and methods: From healthy inhabitants attending health examinations at a medical center in southern Taiwan in 2017, we collected 724 stool samples, which were examined for ESBL-EC fecal carriage using chromogenic medium. ST131 and mcr1-positive E. coli were also investigated using multiplex PCR. Clinical data from all participating adults were collected to analyze the risk factors for fecal ESBL-EC or ST131 E. coli carriage.Results: The prevalence rate of asymptomatic ESBL-EC fecal carriage in adults was 1.9% (14/724). ST131 was found in 22 (3.0%) adults and mcr-1-positive E. coli was found in three (0.4%) adults. A multivariate analysis showed that the risk factors associated with ESBL-EC carriage were diabetes mellitus (adjusted odds ratio [aOR]: 5.5, 95% confidence interval [CI]: 1.3–22.7), a history of colonic polyps (aOR: 6.4, 95% CI: 1.6–24.9), and chronic renal insufficiency (aOR: 20.7, 95% CI: 1.4–305.7). Underlying cancer (aOR: 4.8, 95% CI: 1.0–22.5) and stroke (aOR: 18.0, 95% CI: 1.6–207.5) were associated with ST131 E. coli fecal carriage. In our cohort, travel to Asian countries and food habit were not associated with ST131 or ESBL-EC fecal carriage.Conclusions: The ESBL-EC or ST131 E. coli fecal carriage rate is low among asymptomatic adults in Taiwan. Certain underlying medical conditions were associated with their fecal carriage.Keywords: fecal colonization, extended-spectrum β-lactamase, sequence type, MCR1, Escherichia coli